Game of Prejudice – Experiments at the Extensive and Intensive Margin - Utteeyo Dasgupta; Subha Mani; Joe Vecci; Tomáš Želinský (Global Labor Organization (GLO), 2020)
In an unique lab-in-the-field experiment we design a novel labor market environment, the Game of Prejudice, to elicit preferences for discrimination towards the largest minority group in Europe (the Roma) at the intensive margins as well as at the extensive margins. Our unique experiment design allows us to separate taste-based discrimination from statistical discrimination and examine the impacts of raising the costs of discrimination in such situations. We find discrimination to be commonplace at both margins, with stronger incidence at the extensive margin. We also find higher incidence of taste-based discrimination compared to statistical discrimination. Importantly, we find that when the cost of taste-based discrimination is made sufficiently high, such behaviour disappears at the intensive and extensive margins, providing support for labor market policies that make discrimination very costly for the employer.
Keywords: C9; D3; I1; O1; 330; discrimination; extensive margin; intensive margin; lab-in-the field experiment; Slovakia